Can Time-Varying Currency Risk Hedging Explain Exchange Rates? - Leonie Bräuer; Harald Hau (Center for Economic Studies and ifo Institute (CESifo), 2022)
Over the last decade foreign bond portfolio positions in US dollar assets have risen above the reciprocal US investor positions in foreign currencies. In periods of increased economic uncertainty, institutional investors hedge their international bond positions, which creates a net hedging demand for dollar assets that depreciates USD rates in both the forward and spot markets. We document the time-varying nature of this net hedging demand and show how it relates to eco-nomic uncertainty and the US net foreign bond position in various currencies. Based on a parsimonious VAR model, we find that changes in FX hedging pressure can account for approximately 30% of all monthly variation in the seven most important dollar exchange rates from 2012 to 2022.
Keywords: E44; F31; F32; G11; G15; G23; 330; exchange rate; hedging channel; institutional investors